2021
DOI: 10.1088/1742-6596/1829/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Morphology Properties of the Magnetite ( Fe3O4) Nanoparticles Prepared by Green Method

Abstract: Magnetite nanoparticles have been synthesized by a green method. For this process, ferricchloride hexahydrate, ferrouschloride tetrahydrate (2/1 molar ratio) solution was mixed with different amounts of carob leaves extract and NaOH solution was added to get pH(2, 5,8 and 11) heated for 30 min at (30,60,80 and 100) °C . In this report, a description was introduced for the synthesis of Fe304 nanoparticles (NPs) in order to obtain the optimum (pH8 ,temperature and amount of extract) that have small particle size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The result showed a maximum absorption peak around 350 nm; this indicates the formation of Fe3O4 NPs. Similar UV results for magnetite NPs were found in literature (Yew et al, 2016) (Abdallah et al, 2021) (Sathishkumar et al, 2018).…”
Section: Characterization Of the Green Magnetite Fe3o4 Nanoparticlessupporting
confidence: 90%
“…The result showed a maximum absorption peak around 350 nm; this indicates the formation of Fe3O4 NPs. Similar UV results for magnetite NPs were found in literature (Yew et al, 2016) (Abdallah et al, 2021) (Sathishkumar et al, 2018).…”
Section: Characterization Of the Green Magnetite Fe3o4 Nanoparticlessupporting
confidence: 90%
“…So, the optimum condition for synthesized Fe 2 O 3 NPs is at 70 °C that shows a shorter wavelength with perfect absorbance intensity observed in Figure B. Therefore, the wavelength of 370 nm was selected as an optimum SPR peak at a 70 °C temperature and pH 10 for the synthesis of Fe 2 O 3 NPs …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the wavelength of 370 nm was selected as an optimum SPR peak at a 70 °C temperature and pH 10 for the synthesis of Fe 2 O 3 NPs. 32 3.7. Mechanism for Fe 2 O 3 NPs Synthesis.…”
Section: Xrd Pattern Of Fe 2 O 3 Npsmentioning
confidence: 99%
“…This is due to the increase in the surface area and the scattering of magnetite NPs within the polymer matrix, thus increasing the possibility of radiation interaction with the material, absorbing the energy of the photon, and this agrees with findings in Refs. [54,55]. The effect of the operating voltage can be seen from the values of the attenuation properties in Figures 12-15 and it is found that by increasing the voltage values, the ability of the nanocomposite to attenuate the rays decreases.…”
Section: The Effect Of the Size Of Magnetite Nps On The X-ray Attenua...mentioning
confidence: 97%